The Risk Of Seizure-Related Hospitalization Among Older Adults On Levetiracetam Monotherapy: A Retrospective Comparative Cohort Study - Alzahrani H (Dove Medical Press, 2019)
Huda Alzahrani,1 Haya Mohammad Almalag,2 Yazed AlRuthia,2,3 Fawaz Al-hussain,4 Bander Balkhi,2,3 Lama Almutairi,1 Reem Algasem,5 Edward B De Vol,6 Manal Rashed Almarzouqi,6 Abdulaziz Alsemari7 1Department of Pharmacy, King Saud University Medical City, Riyadh, Saudi Arabia; 2Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Pharmacoeconomics Research Unit, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 4Department of Medicine, Neurology Division, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 5Department of Pharmaceutical Care, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 6Department of Epidemiology and Scientific Computing, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia; 7Department of Neurosciences, King Faisal Specialist Hospital and Research Centre, Riyadh, Kingdom of Saudi ArabiaCorrespondence: Yazed AlRuthiaDepartment of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi ArabiaTel +996 11 4677483Fax +966 11 4677480Email yazeed@ksu.edu.saBackground: Antiepileptic drug monotherapy is the mainstay of treatment for epilepsy; however, the efficacy of different antiepileptic drugs in reducing the incidence of seizure-related hospitalization among older adults, who are at higher risk of developing epilepsy compared to their younger counterparts, has not been examined.Purpose: The objective of the present study was to compare the rate of seizure-related hospitalization among older adults on levetiracetam compared to different antiepileptic drugs (AEDs).Patients and methods: This was a retrospective cohort study of older adults (≥60 years) in two tertiary care hospitals. Patients who are 60 years of age and older, have a confirmed diagnosis of epilepsy, and are taking a single and the same antiepileptic drug for at least 36 months were included. The patients were followed up for 24 months after 12 months of treatment with no incidence of seizure-related hospitalization via their health records. Multiple Poisson regression with robust error variance was used to estimate the relative risk of hospitalization for patients on levetiracetam compared to different antiepileptic drugs controlling for age, gender, number of prescription medications, dosage strengths, and Charlson Comorbidity Index (CCI) score.Results: One hundred and thirty-six patients met the inclusion criteria and were included in the study. The recruited patients were on one of the following four antiepileptic drugs: carbamazepine (n=44), levetiracetam (n=39), phenytoin (n=31), and valproic acid (n=22). Patients on levetiracetam were more than twice as likely to be hospitalized due to seizures within the 24 months of follow-up compared to their counterparts on other AEDs (RR=2.76, 95% CI=1.16–6.53, P=0.021).Conclusion: This study suggests that older adults on old generation AEDs such as phenytoin, carbamazepine, and valproic acid appear to have a lower risk of seizure-related hospitalization compared to their counterparts on levetiracetam.Keywords: seizures, hospitalization, levetiracetam, carbamazepine, phenytoin, valproic acid